Mid-infrared-scanning cavity ring-down CH2F2 detection using electronically tuned Cr:ZnSe laser - Masaki Yumoto; Yasushi Kawata; Satoshi Wada (Scientific Reports, 2022)
Abstract The development of mid-infrared (mid-IR) tunable lasers has been driving various laser spectroscopic technologies. Herein, we report wavelength-scanning cavity ring-down spectroscopy (WS-CRDS) in the mid-IR region using an electronically tuned Cr:ZnSe (ET-Cr:ZnSe) laser, which could achieve a nanosecond pulse operation, with broad wavelength tuning of 2–3 µm. This allowed WS-CRDS-induced trace detection of the refrigerant, CH2F2. A CH2F2 detection limit of 0.66 ppm (3σ), and the detection of trace H2O in CH2F2 was realized using the broad wavelength-tuning range feature, demonstrating the effectiveness of the ET-Cr:ZnSe laser in WS-CRDS. We believe that our method would accelerate the development of various trace-gas detection technologies.